No effects of tactile stimulation on welfare indicators of Saanen goat kids: a pilot study - Andrioli, Mayara; Grajales-Cedeño , Joseph Kaled; Carvalhal, Monique Valéria de Lima; Costa, Mateus José Rodrigues Paranhos da (Acta Scientiarum. Animal Sciences, 2024)
This study aimed to evaluate the effects of tactile stimulation on the welfare of goat kids. Thirty-six goat kids were allocated into three treatments as follows: TSG = taking the goat kids out of the cage every day when they received tactile stimulation, RCG = taking the goat kids out of the cage for 5 s, and NRS = not taking the goat kids out of the cage nor receiving tactile stimulation. TSG goat kids received tactile stimulation once a day, for two minutes, from the 3rd to the 40th day. Goat kids’ welfare was assessed by considering performance, health, and behavioral indicators. During the voluntary approach test, 96.5% of the goat kids voluntarily approached familiar and unfamiliar humans. There were significant effects only on the interaction between treatment and age on time spent in the corners and time playing (KW = 27.54 and 47.83, p < 0.01, respectively). We conclude that tactile stimulation did not affect any of the welfare indicators addressed in this study.